2014
DOI: 10.1039/c3ra47407k
|View full text |Cite
|
Sign up to set email alerts
|

Reduction with tris(2-carboxyethyl)phosphine (TCEP) enables the use of an S-sulphonate protecting group for thiol-mediated bioconjugation

Abstract: Herein, we demonstrate the effectiveness of the water-friendly Ssulphonate group as an alternative to traditional thiol protecting groups for subsequent deprotection-bioconjugation reactions, under conditions that are compatible with the use of biochemical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The 1-thio sugars have attracted increasing attention and interest as a building block in the synthesis of glyco-conjugates especially for the modification of proteins by an oligosaccharide . Reduction of the unprotected β-glucosyl Bunte salt with tris­(2-carboxyethyl) phosphine hydrochloride (TCEP-HCl) afforded the corresponding 1-thioglucose in 70% yield (Figure a). It should be noted that we were able to prepare 1-thio sugars through a one-pot process via glycosyl Bunte salt intermediates, starting from unprotected sugars.…”
mentioning
confidence: 99%
“…The 1-thio sugars have attracted increasing attention and interest as a building block in the synthesis of glyco-conjugates especially for the modification of proteins by an oligosaccharide . Reduction of the unprotected β-glucosyl Bunte salt with tris­(2-carboxyethyl) phosphine hydrochloride (TCEP-HCl) afforded the corresponding 1-thioglucose in 70% yield (Figure a). It should be noted that we were able to prepare 1-thio sugars through a one-pot process via glycosyl Bunte salt intermediates, starting from unprotected sugars.…”
mentioning
confidence: 99%
“…The results observed here are consistent with previous observations that TCEP indeed reacts with maleimide to generate a phosphorus-containing adduct; however, it is proposed here that this adduct is closer in structure to the neutral ylene rather than the phosphonium ylide proposed previously. [27][28][29] Scheme 2. Reaction of lysine derivatized maleimide (5) with TCEP (1) and THPP (2).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Contrary to this however, a number of groups have reported decreased yields of conjugation when using maleimide in the presence of TCEP, suggesting possible reaction between the two reagents. [25][26][27][28] Recently, Sánchez et al have reported the observation of a phosphonium-ion adduct between TCEP and maleimide on the basis of mass spectrometry, though this adduct was not fully characterised. 28 In this study we demonstrate that the water soluble phosphine reducing agents TCEP and THPP both react rapidly with maleimides and phenyl vinyl sulfone under conditions typically employed for bioconjugation reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Many others have since then confirmed the early observations, showing that an excess of the reducing agent is detrimental to one-pot thiol chemistry. 31,32,41,42 Conversely, TCEP has been used successfully in one-pot thiol chemistry with other alkenes, including vinyl sulfone, 43 vinyl phenyl, 44 and acrylate 45 moieties, and not only as reducing agent but as a catalyst for the thiol−ene reaction. In our study, it however appeared that an excess amount of TCEP is also detrimental for thiol/vinyl sulfone conjugation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%